2017
DOI: 10.1039/c6ta10316b
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the electrocatalytic activity of MoS2 across its amorphous to crystalline transition

Abstract: A systematic mapping of the electrocatalytic activity of MoS2 across a structural transformation allows for correlation of structure to function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 68 publications
3
50
0
3
Order By: Relevance
“…Through irradiation with the two‐subpulse train, the ratio of Mo V defect species could be maximized and the ratio of bridging and terminal S 2 2− ligands could be controlled, which resulted in the a‐MoS x ‐250/10 catalysts possessing excellent HER catalytic activity with a low Tafel slope of 40 mV dec −1 , a high C dl of 74.47 mF cm −2 , a large j 250 of 516 mA cm −2 , and relatively good stability. The HER catalytic activity of the a‐MoS x ‐250/10 materials in this study is comparable with that of the a‐MoS x materials prepared using other reported methods, which are listed in Table S1 (Supporting Information).…”
Section: Resultssupporting
confidence: 75%
“…Through irradiation with the two‐subpulse train, the ratio of Mo V defect species could be maximized and the ratio of bridging and terminal S 2 2− ligands could be controlled, which resulted in the a‐MoS x ‐250/10 catalysts possessing excellent HER catalytic activity with a low Tafel slope of 40 mV dec −1 , a high C dl of 74.47 mF cm −2 , a large j 250 of 516 mA cm −2 , and relatively good stability. The HER catalytic activity of the a‐MoS x ‐250/10 materials in this study is comparable with that of the a‐MoS x materials prepared using other reported methods, which are listed in Table S1 (Supporting Information).…”
Section: Resultssupporting
confidence: 75%
“…The two spikes in the red curve after 1400 s and 6500 s appear after refreshing the electrolyte. We tentatively attribute their presence to a small fraction of oxygen 18 O (natural abundance: 0.2%) in the form of 16 O- 18 O molecules (m = 34 g/mol) that are dissolved in the refreshed electrolyte. The electrolyte is degassed within a minute or so, after which the spikes disappear.…”
Section: Electrocatalytic Performancementioning
confidence: 93%
“…By contrast, the MoS 2 (008) reflection was visible in both the unmodified and Ag+Pd/VA‐MoS 2 samples, indicating that these electrodes had similar crystallinity. Although MoS 2 with lower crystallinity could lead to a higher density of active sites, it also simultaneously leads to poor conductivity; the latter would significantly impact performance of the electrodes in this study owing to their thickness. The alternative explanation, that the Pd/VA‐MoS 2 was preferentially oriented in a different direction, thus explaining the absence of the MoS 2 (008) peak.…”
Section: Resultsmentioning
confidence: 98%